2018
DOI: 10.1002/advs.201800222
|View full text |Cite
|
Sign up to set email alerts
|

Cold Vapor Generation beyond the Input Solar Energy Limit

Abstract: Abstract100% efficiency is the ultimate goal for all energy harvesting and conversion applications. However, no energy conversion process is reported to reach this ideal limit before. Here, an example with near perfect energy conversion efficiency in the process of solar vapor generation below room temperature is reported. Remarkably, when the operational temperature of the system is below that of the surroundings (i.e., under low density solar illumination), the total vapor generation rate is higher than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
232
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(236 citation statements)
references
References 40 publications
(70 reference statements)
1
232
0
Order By: Relevance
“…Besides developing low‐cost photothermal materials, it is of paramount importance to design solar steaming‐collection systems that can be efficient as well as portable to address the needs of people on individual levels. 3D superstructures with large surface areas, which are often designed for energy and environment applications, have also demonstrated enhanced water evaporation rates due to the improved transpiration pathways compared to 2D structures . Some 3D solar steamers also exploit environmental energy and reach 100% efficiency in solar‐to‐vapor energy transfer .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides developing low‐cost photothermal materials, it is of paramount importance to design solar steaming‐collection systems that can be efficient as well as portable to address the needs of people on individual levels. 3D superstructures with large surface areas, which are often designed for energy and environment applications, have also demonstrated enhanced water evaporation rates due to the improved transpiration pathways compared to 2D structures . Some 3D solar steamers also exploit environmental energy and reach 100% efficiency in solar‐to‐vapor energy transfer .…”
mentioning
confidence: 99%
“…3D superstructures with large surface areas, which are often designed for energy and environment applications, have also demonstrated enhanced water evaporation rates due to the improved transpiration pathways compared to 2D structures . Some 3D solar steamers also exploit environmental energy and reach 100% efficiency in solar‐to‐vapor energy transfer . Despite high solar–thermal conversion efficiencies and water evaporation rates shown in some studies, the amount of actually collected clean water can be greatly compromised once the solar steamers are utilized in a steam‐collection setup.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[121] In this case, due to the special configuration of vertical cylinder solar absorber, the temperature of side surface was lower than that of top side surfaces and even environmental temperature, because most of solar energy was absorbed by the top surface. [127] To the best of our knowledge, the above two cases are the first time to realize a net energy gain (i.e., low-grade heat) from the environment during solar steam generation, with great implication for the development of high-performance solar steam generation. Thus, this solar generator can obtain higher enhancement factor and yield an evaporation rate exceeding the theoretical value (100% solar-to-vapor energy transfer efficiency under 100 mW cm 2 of solar illumination).…”
Section: Strategies For Enhancing Water Evaporation Efficiencymentioning
confidence: 99%
“…Until now, there are only a few examples of solar steam generation device with 100% solar-to-vapor energy transfer efficiency, in spite of the implantation of some advanced strategies such as energy gain from environment to improve thermal management, [121,127] and 3D photothermal structure design to boost utilization of solar energy and minimize heat losses. The previous reports found that most solar steam generator devices exhibited a low water evaporation rate in the range of 1.0-1.5 kg m −2 h −1 under one sun illumination, and just a few cases can reach or exceed 2.0 kg m −2 h −1 .…”
Section: Challengesmentioning
confidence: 99%